2016
DOI: 10.1016/j.adolescence.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of self‐control at the transition to secondary school: Considering the role of pubertal status and parenting

Abstract: Higher self-control in children and adolescents is associated with a range of positive outcomes in adulthood. However, little is known about the naturalistic development of self-control during early adolescence and the factors that affect this. We examined the role of puberty and parenting style as theoretically important influences on stability and change in self-control. A longitudinal (3 waves), multiple-informant dataset of children entering early adolescence (M = 11 years) was used to explore longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 85 publications
(102 reference statements)
2
55
0
4
Order By: Relevance
“…The variations recorded in the transition to high school show a small reduction in prosocial behaviors and a significant, but weaker, decrease in hyperactivity/attention. Concerning hyperactivity, the weakness of the transition-related effect may be partly due to normative developmental changes in the executive functions linked with self-regulation, which appear to plateau during in early to mid-adolescence (Ng-Knight et al, 2016), and the relatively short time-span in which observations took place. For the other dimensions examined by the SDQ, instead, there were no significant variations.…”
Section: Discussionmentioning
confidence: 99%
“…The variations recorded in the transition to high school show a small reduction in prosocial behaviors and a significant, but weaker, decrease in hyperactivity/attention. Concerning hyperactivity, the weakness of the transition-related effect may be partly due to normative developmental changes in the executive functions linked with self-regulation, which appear to plateau during in early to mid-adolescence (Ng-Knight et al, 2016), and the relatively short time-span in which observations took place. For the other dimensions examined by the SDQ, instead, there were no significant variations.…”
Section: Discussionmentioning
confidence: 99%
“…Applying Baumrind's and Maccoby and Martin's definition of parenting styles (10,11), constraints could include: (i) insufficient opportunities to exert self-regulation as characterized by the low demandingness of neglectful or permissive parents; and (ii) too many expectations that override child self-control as characterized by the unresponsive demandingness of authoritarian parents. Indeed, observational studies have supported this resource model of self-control and demonstrated the associations of permissive, neglectful and authoritarian parenting with low self-control (19)(20)(21), as well as the relationship between authoritative parenting and high self-control (15)(16)(17)22). Studies have also demonstrated an association between neglectful parenting and higher rates of depression and poorer psychosocial development (15,22).…”
Section: Introductionmentioning
confidence: 89%
“…Rice et al (2011) also argue that the focus of research on the first year of secondary school is inappropriate, as transition will likely happen over a longer period of time with children needing this extended time to adapt. However, most studies, including their own, have collected data at two time points (Jindal-Snape & Foggie, 2008;Jindal-Snape & Miller, 2008;Rice et al, 2011;Waters et al, 2014a) and where data were collected over three points, this was usually either over two school years within a 12-month period (Jindal-Snape et al, 2011) or across one school year within a 12-month period (Ng-Knight et al, 2016). West et al (2010) and Benner and Graham (2009) are an exception, as their studies span a number of years.…”
Section: Methodsmentioning
confidence: 99%